Mechanisms for Development of Ciprofloxacin Resistance in a Clinical Isolate of Pseudomonas aeruginosa - Xu, Congjuan; Liu, Huimin; Pan, Xiaolei; Ma, Zhenzhen; Wang, Dan; Zhang, Xinxin; Zhu, Guangbo; Bai, Fang; Cheng, Zhihui; Wu, Weihui; Jin, Yongxin (Frontiers in Microbiology, 2021)
Treatment of infections by Pseudomonas aeruginosa is difficult due to its high intrinsic and acquired antibiotic resistance. Upon colonization in the human hosts, P. aeruginosa accumulates genetic mutations that confer the bacterium antibiotic resistance and ability to better live in the host environment. Charactering the evolutionary traits would provide important insights into the development of effective combinatory antibiotic therapies to cure P. aeruginosa infections. In the work, we performed a detailed analysis of the molecular mechanisms by which a clinical isolate (CSP18) yields a ciprofloxacin-resistant derivative (CRP42). Genomic DNA re-sequencing and RNAseq were carried out to compare the in vivo evolutionary trajectories and transcriptional profiles between the two isolates. The results indicated that D87G mutation in GyrA together with MexEF-OprN hyper-expression caused by F7S mutation in MexS were responsible for the increased resistance to ciprofloxacin in the isolate CRP42. Further simulation of CRP42 by gene editing in CSP18 demonstrated that D87G mutation in GyrA rendered CSP18 a 4-fold increase in MIC against ciprofloxacin, while F7S mutation in MexS conferred an additional 8-fold increase. Our experimental results demonstrate for the first time that the clinically relevant F7S point mutation in MexS results in hyper-expression of the mexEF-oprN and thus confer P. aeruginosa resistance to ciprofloxacin.